Tantalum carbide coating

By forming a double-layer tantalum carbide coating on the surface of the graphite crucible, the problem of prone to cracking and peeling of the existing coating is solved, high bonding strength and corrosion resistance are achieved, and the service life is extended and crystal contamination is avoided.

CN119638428BActive Publication Date: 2025-04-15NAT UNIV OF DEFENSE TECH
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202510184119.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-02-19
Publication Date
2025-04-15
Estimated Expiration
2045-02-19

AI Technical Summary

Technical Problem

The tantalum carbide coating on the surface of existing graphite crucibles has a single structure and is prone to cracking and peeling, resulting in limited service life and insufficient corrosion resistance.

Method used

A tantalum carbide coating with a double-layer structure is TaC of equiaxed crystal, with a thickness of 3 μm to 5 μm and an outer layer is Ta2C of columnar crystal, with a thickness of 5 μm to 10 μm. This bilayer structure is formed on the graphite surface through high-temperature reaction and atomic diffusion technology.

Benefits of technology

It improves the bonding strength and corrosion resistance of the tantalum carbide coating, extends the service life, and effectively inhibits the outward diffusion of graphite, avoids crystal pollution.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119638428B_ABST
    Figure CN119638428B_ABST
Patent Text Reader

Abstract

The invention discloses a tantalum carbide coating, belonging to the technical field of ceramic coatings. The tantalum carbide coating of the invention comprises an inner and outer layer, wherein the inner layer is TaC equiaxed crystals and the outer layer is Ta2C columnar crystals. The tantalum carbide coating of the invention has the characteristics of high bonding strength, good corrosion resistance, and not easy to crack, and can be applied to the coating of graphite crucibles for growing third-generation semiconductor single crystals.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of ceramic coatings, and in particular relates to a tantalum carbide coating. Background Art

[0002] The growth of third-generation semiconductor crystals represented by silicon carbide is carried out under extreme environments such as ultra-high temperature (over 2000°C), long time, and chemical corrosion, which places extremely high demands on the crucible materials used for semiconductor crystal growth.

[0003] Graphite is a commonly used crucible material for the growth of third-generation semiconductor crystals, with its wide sources, low cost, and easy processing. However, graphite crucibles are easily corroded by corrosive gases in the crystal growth environment, which limits their service life and even causes contamination of the grown crystals. Therefore, the surface of the graphite crucible urgently needs to be protected by an anti-corrosion coating.

[0004] Tantalum carbide (TaC) has excellent properties such as high melting point, high strength, good stability, and chemical corrosion resistance. It is an excellent candidate material for corrosion-resistant coatings in the field of high-temperature corrosion and is also often used in the field of semiconductor crystal growth graphite crucible coatings. At present, there are mainly two types of tantalum carbide coatings on graphite surfaces. One is to deposit TaC coatings on the graphite surface by chemical vapor deposition (Zhang Li, Qi Haitao, Xu Yongkuan, et al. Preparation of dense tantalum carbide coatings by high-temperature chemical vapor deposition. Functional Materials, 2017, 6(48): 06183-06186), and the other is to prepare TaC coatings on the graphite surface by slurry coating combined with high-temperature sintering (D. Nakamura, A. Suzumura, K. Shigetoh. Sintered tantalum carbide coatings on graphite substrates: Highly reliable protective coatings for bulk and epitaxial growth. Applied Physics Letters, 2015, 106: 082108).

[0005] Both coatings are single-layer structures, and the physical phase is TaC. The difference is that the former is a columnar crystal structure, and the latter is an equiaxed crystal structure. The columnar crystal structure coating has better thermal shock resistance, but it is easy to crack in the thickness direction of the coating. The equiaxed crystal structure coating is not easy to crack, but the thermal shock resistance is poor, which makes the tantalum carbide coating on the graphite surface easy to peel off and fail, and the service life is limited. Summary of the invention

[0006] In view of the problem that the tantalum carbide coating in the prior art has a single structure and is prone to cracking, peeling and failure, the present invention provides a tantalum carbide coating, which is a thin layer present on the surface of a graphite material. The tantalum carbide coating has the advantages of high bonding strength and good corrosion resistance, and is applied in the field of third-generation semiconductor crystal growth crucibles.

[0007] The purpose of the present invention is achieved through the following technical solutions:

[0008] A tantalum carbide coating comprises an inner and outer layer: the inner layer is equiaxed crystals, and the outer layer is columnar crystals;

[0009] The phase of the equiaxed crystal is TaC, and the thickness is 3 μm to 5 μm;

[0010] The columnar crystal phase is Ta2C, and the thickness is 5μm~10μm;

[0011] The method for preparing the tantalum carbide coating comprises the following steps:

[0012] (1) Weigh Ta powder, LiCl powder, and KF powder according to a mass ratio of (3.0-9.0):(21.4-30):(26.1-30), and grind and mix the three raw materials evenly to obtain a mixed powder;

[0013] (2) placing the obtained mixed powder and graphite in a crucible so that the mixed powder covers the graphite, and then moving it into a high-temperature furnace;

[0014] (3) The high-temperature furnace is heated to 800°C~900°C and the holding time is 3h~5h. During this process, the graphite directly reacts with the reactants in the mixed powder (i.e., molten salt) to form a TaC equiaxed crystal pre-coating. Then, the temperature is further heated to 1000°C~1200°C and the holding time is 2h~4h. During this process, due to the obstruction of the TaC equiaxed crystal pre-coating, the graphite cannot directly react with the reactants in the mixed powder. It needs to pass through the TaC equiaxed crystal pre-coating through atomic diffusion and then react with the reactants in the mixed powder, thereby growing a Ta2C columnar crystal layer on the surface of the TaC equiaxed crystal pre-coating, and then cooling to room temperature with the furnace;

[0015] (4) washing the crucible with water to obtain a tantalum carbide coating;

[0016] The tantalum carbide coating has the following properties:

[0017] ①The bonding strength of the coating is ≥8MPa;

[0018] ②The mass loss rate of the coating in the SiC single crystal growth environment is ≤0.3g / m 2 ·h.

[0019] Furthermore, in step (1), the Ta powder, LiCl powder and KF powder are weighed in a mass ratio of 3.0:21.4:26.1.

[0020] Furthermore, in step (2), there is no fixed ratio between the mixed powder and graphite. The main purpose is to make a coating on the graphite surface. For example, if a graphite plate is thicker, the amount of mixed powder used is larger so that the mixed powder covers the graphite. The thickness of the tantalum carbide coating finally prepared remains unchanged.

[0021] Compared with the prior art, the present invention has the following beneficial effects:

[0022] 1. The tantalum carbide coating described in the present invention combines the advantages of columnar crystal structure and equiaxed crystal structure, and has not only a simple structure but also high bonding strength and is not prone to cracking.

[0023] 2. The tantalum carbide coating of the present invention can not only improve the high-temperature corrosion resistance of the graphite crucible, but also inhibit the outward diffusion of carbon in the graphite through the absorption and barrier effect of the double-layer tantalum carbide, thereby avoiding contamination of the grown crystals. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on the structures shown in these drawings without paying creative work.

[0025] Figure 1 This is a schematic diagram of the structure of the tantalum carbide coating of Example 1 of the present invention (wherein: 1, graphite substrate; 2, equiaxed crystals; 3, columnar crystals);

[0026] Figure 2 This is a scanning electron microscope photograph of the tantalum carbide coating of Example 1 of the present invention;

[0027] Figure 3 This is the XRD spectrum of the tantalum carbide coating of Example 1 of the present invention;

[0028] Figure 4 This is a scanning electron microscope photograph of the tantalum carbide coating of Example 2 of the present invention. DETAILED DESCRIPTION

[0029] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0030] Embodiment 1:

[0031] A tantalum carbide coating comprises an inner and outer layer: the inner layer is equiaxed crystals, and the outer layer is columnar crystals;

[0032] The phase of the equiaxed crystal is TaC, and the thickness is 3 μm;

[0033] The columnar crystal phase is Ta2C, and the thickness is 5 μm;

[0034] The method for preparing the tantalum carbide coating comprises the following steps:

[0035] (1) Weigh 3 g of Ta powder, 21.4 g of LiCl powder, and 26.1 g of KF powder, place them in a mortar and grind them evenly to obtain a mixed powder;

[0036] (2) Place the mixed powder and graphite in a crucible, and make the mixed powder cover the graphite, and then move it to a high-temperature furnace;

[0037] (3) The high-temperature furnace is heated to 800°C and kept at this temperature for 3 hours. During this process, graphite directly reacts with the reactants in the mixed powder to form a TaC equiaxed crystal pre-coating layer. The furnace is then heated to 1000°C and kept at this temperature for 3 hours. During this process, due to the obstruction of the TaC equiaxed crystal pre-coating layer, graphite cannot directly react with the reactants in the mixed powder, but needs to pass through the TaC equiaxed crystal pre-coating layer through atomic diffusion and then react with the reactants in the mixed powder, thereby growing a Ta2C columnar crystal layer on the surface of the TaC equiaxed crystal pre-coating layer, and finally cooling with the furnace.

[0038] (4) Cleaning the crucible with water to obtain a tantalum carbide coating sample;

[0039] The tantalum carbide coating has the following properties:

[0040] ①The coating bonding strength is 9MPa;

[0041] ②The mass loss rate of the coating in the SiC single crystal growth environment is 0.2g / m 2 ·h.

[0042] Figure 1 Schematic diagram of the structure of the tantalum carbide coating prepared in Example 1, as shown in Figure 1As shown, 1 is graphite matrix, 2 is TaC equiaxed crystal, and 3 is Ta2C columnar crystal;

[0043] Figure 2 This is a scanning electron microscope picture of the tantalum carbide coating prepared in Example 1. Figure 2 As shown, the inner layer of the coating is equiaxed crystal with a thickness of 3 μm, and the outer layer is a columnar crystal structure with a thickness of 5 μm;

[0044] Figure 3 The XRD spectrum of the tantalum carbide coating prepared in Example 1 is as follows: Figure 3 As shown, the coating mainly contains two phases, TaC and Ta2C.

[0045] Embodiment 2:

[0046] A tantalum carbide coating comprises an inner and outer layer; the inner layer is equiaxed crystals and the outer layer is columnar crystals;

[0047] The phase of the equiaxed crystal is TaC, and the thickness is 5 μm;

[0048] The columnar crystal phase is Ta2C, and the thickness is 10 μm;

[0049] The method for preparing the tantalum carbide coating comprises the following steps:

[0050] (1) Weigh 9 g of Ta powder, 21.4 g of LiCl powder, and 26.1 g of KF powder, place them in a mortar and grind them evenly to obtain a mixed powder;

[0051] (2) Place the mixed powder and graphite in a crucible, and make the mixed powder cover the graphite, and then move it to a high-temperature furnace;

[0052] (3) The high-temperature furnace is heated to 900°C and kept at this temperature for 5 hours. During this process, graphite directly reacts with the reactants in the mixed powder to form a TaC equiaxed crystal pre-coating. The furnace is then heated to 1200°C and kept at this temperature for 4 hours. During this process, due to the obstruction of the TaC equiaxed crystal pre-coating, graphite cannot directly react with the reactants in the mixed powder, but needs to pass through the TaC equiaxed crystal pre-coating through atomic diffusion and then react with the reactants in the mixed powder, thereby growing a Ta2C columnar crystal layer on the surface of the TaC equiaxed crystal pre-coating, and finally cooling with the furnace.

[0053] (4) Cleaning the crucible with water to obtain a tantalum carbide coating sample;

[0054] The tantalum carbide coating has the following properties:

[0055] (1) The coating bonding strength is 10MPa;

[0056] (2) The mass loss rate of the coating in the SiC single crystal growth environment is about 0.1g / m2 ·h.

[0057] Figure 4 This is a scanning electron microscope image of the tantalum carbide coating prepared in Example 2. Figure 4 As shown, the inner layer of the coating is an equiaxed crystal with a thickness of 5 μm, and the outer layer is a columnar crystal structure with a thickness of 10 μm.

[0058] Comparative Example 1:

[0059] A tantalum carbide coating, wherein the tantalum carbide coating is a single-layer equiaxed crystal;

[0060] The phase of the single-layer equiaxed crystal is TaC, and the thickness is 8 μm;

[0061] The method for preparing the tantalum carbide coating comprises the following steps:

[0062] (1) Weigh 10 g of TaCl5 powder, 3 mL of acetylacetone, and 70 mL of ethanol, and mix and dissolve the three ingredients thoroughly to obtain a mixed solution;

[0063] (2) placing the mixed solution in a hydrothermal reactor for treatment at a temperature of 200°C for 5 hours to obtain a precursor powder;

[0064] (3) Placing the obtained precursor powder on the graphite surface to obtain a pre-coated graphite;

[0065] (4) The pre-coated graphite is placed in a high-temperature furnace for treatment at a temperature of 2000°C for 1 hour to obtain a TaC coating.

[0066] The bonding strength of the TaC coating obtained in Comparative Example 1 is 6 MPa, which is lower than the bonding strength of the TaC coating obtained in Example 1.

[0067] Comparative Example 2:

[0068] A tantalum carbide coating, wherein the tantalum carbide coating is a single layer of columnar crystals;

[0069] The phase of the single-layer columnar crystal is TaC, and the thickness is 15 μm;

[0070] The method for preparing the tantalum carbide coating comprises the following steps:

[0071] (1) Weigh 50 g of TaCl5 powder and place it in a vacuum gasification device for treatment at a temperature of 180°C to obtain TaCl5 gas;

[0072] (2) TaCl5 gas, Ar gas, and H2 were introduced into a high-temperature furnace containing a graphite sample at a volume ratio of 1:1:1. The temperature of the high-temperature furnace was set at 2000°C and the reaction lasted for 5 hours to obtain a TaC coating.

[0073] The mass loss rate of the TaC coating obtained in Comparative Example 2 in the SiC single crystal growth environment is 0.5 g / m 2 h, which is higher than the mass loss rate of the TaC coating obtained in Example 2.

[0074] Results and Discussion:

[0075] 1. By comparing the embodiment and comparative example 1, it is shown that the tantalum carbide coating prepared by the present invention is a double-layer tantalum carbide coating with higher bonding strength. Since the inner equiaxed crystal TaC layer is generated by reaction, the bonding between the coating and the substrate is a strong chemical bond, while the single-layer equiaxed crystal TaC layer in comparative example 1 is mainly a physical bond.

[0076] 2. By comparing the embodiment and comparative example 2, it is shown that the double-layer tantalum carbide coating prepared by the present invention has higher corrosion resistance. This is mainly due to the fact that the outer columnar crystal Ta2C layer has good thermal shock resistance, while the inner equiaxed crystal TaC layer is not easy to crack, making it difficult for the corrosive gas growing SiC single crystal to penetrate the coating and corrode the graphite substrate.

[0077] It is to be understood that the present invention is described by some embodiments, and it is known to those skilled in the art that various changes or equivalent substitutions may be made to these features and embodiments without departing from the spirit and scope of the present invention. In addition, under the teachings of the present invention, these features and embodiments may be modified to adapt to specific circumstances and materials without departing from the spirit and scope of the present invention. Therefore, the present invention is not limited by the specific embodiments disclosed herein, and all embodiments falling within the scope of the claims of this application are within the scope of protection of the present invention.

Claims

1. A tantalum carbide coating, characterized in that: It consists of two layers: the inner layer is equiaxed crystals, and the outer layer is columnar crystals; The phase of the equiaxed crystal is TaC, and the thickness is 3 μm to 5 μm; The columnar crystal phase is Ta2C, and the thickness is 5μm~10μm; The method for preparing the tantalum carbide coating comprises the following steps: (1) Weigh Ta powder, LiCl powder, and KF powder according to a mass ratio of (3.0-9.0):(21.4-30):(26.1-30), and grind and mix the three raw materials evenly to obtain a mixed powder; (2) placing the obtained mixed powder and graphite in a crucible so that the mixed powder covers the graphite, and then moving it into a high-temperature furnace; (3) The high-temperature furnace is heated to 800°C~900°C and the holding time is 3h~5h. The graphite directly reacts with the reactants in the mixed powder to form a TaC equiaxed crystal pre-coating layer. Then, the temperature is further heated to 1000°C~1200°C and the holding time is 2h~4h. The graphite passes through the TaC equiaxed crystal pre-coating layer by atomic diffusion and then reacts with the reactants in the mixed powder. Then, a Ta2C columnar crystal layer is grown on the surface of the TaC equiaxed crystal pre-coating layer, and then the Ta2C columnar crystal layer is cooled to room temperature with the furnace. (4) washing the crucible with water to obtain a tantalum carbide coating; The tantalum carbide coating has the following properties: ①The bonding strength of the coating is ≥8MPa; ②The mass loss rate of the coating in the SiC single crystal growth environment is ≤0.3g / m 2 ·h.

2. A tantalum carbide coating according to claim 1, characterized in that: In step (1), the Ta powder, LiCl powder and KF powder are weighed in a mass ratio of 3.0:21.4:26.1.

Citation Information

Patent Citations

  • Coated cutting tool insert

    CN101218371A

  • Tantalum-based anti-corrosion protective composite coating and preparation method and application thereof

    CN111647862A